Leadership management in quality improvement of sd muhammadiyah wirobrajan 3 - Muh Nur Fuadi; Roihan Sadad (At Turots: Jurnal Pendidikan Islam, 2025)
Efforts to improve the quality of education require serious consideration from various parties. The problem of low quality of education is an issue that must be addressed immediately so that improvements can be made in various sectors, especially management, in order to improve the quality of education. This study analyzes leadership management of; la schools in an effort to improve the quality of education. The research method used in this study is a descriptive qualitative analysis. The results showed that the principal combined transformational and participatory leadership theories to protect the school community. The efforts made by the principal are in the form of performance evaluation, holding training or workshops and good cooperation with parents. It is hoped that in the future, further research can examine the quality of education based on aspects of school infrastructure.